СВ. ФРАНЦИСК АССИЗСКИЙ С ТОЧКИ ЗРЕНИЯ ФИЛОСОФСКОЙ АНТРОПОЛОГИИ: МОДЕРНИЗМ И ПОСТМОДЕРНИЗМ - ГОЛОЗУБОВ, А. В. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science", 2015)
Интерес к св. Франциску Ассизскому проявился как в эпоху модернизма, так и в более широкой культурной ситуации постмодерна. Св. Франциск занял важное место в теоретических работах из области философской антропологии и в практическом осмыслении философско-антропологических феноменов, таких как радость, смех, свобода, удивление. Христоцентричная антропология св. Франциска была противопоставлена антропологии доминирования. Голозубов О.В. СВ. ФРАНЦИСК АССІЗЬКИЙ З ТОЧКИ ЗОРУ ФІЛОСОФСЬКОЇ АНТРОПОЛОГІЇ: МОДЕРНІЗМ І ПОСТМОДЕРНІЗМ Інтерес до св. Франциска Ассизького проявляється як в епоху модернізму, так і в більш широкій культурній ситуації постмодерну. Св. Франциск зайняв важливе місце в теоретичних роботах з області філософської антропології і в практичному осмисленні філософсько- антропологічних феноменів, як радість, сміх, свобода, здивування. Христоцентрична антропологія св. Франциска була протиставлена антропології домінування. Ключові слова: св. Франциск Ассізький, францисканство, модернізм, постмодернізм, філософська антропологія, радість, свобода. Golozubov AV ST. FRANCIS OF ASSISI FROM THE POINT OF VIEW OF PHILOSOPHICAL ANTHROPOLOGY: MODERNISM AND POSTMODERNISM In the article St. Francis has been considered from the standpoint of the history and content of philosophical anthropology. In his life and preaching such fundamental to the philosophy of the human being as joy and laughter, wonder and freedom can be found. Image of St. Francis has been actualized both in the modern epoch and in the wider cultural postmodern situation. His personality and phenomenon of the Franciscanism in the whole play an important role in finding ways of interacting between anthropology and theology in its updated postmodern version. Both waves of interest to the saint from Assisi in the twentieth century coincided with the growing problem of a man and at the same time appeal to the medieval discourse. Refuse of the concept of the Dark Ages in the situation of modernism / postmodernism led to the rehabilitation of the medieval intellectual culture and therefore carnival comic elements. In this sense interpretation of St. Francis in the novels of N. Kazantzakis, U. Eco etc. looks relevant. St. Francis took an important place in the philosophical and anthropological discourse, starting with Max Scheler, in theoretical writings in the field of the philosophical anthropology, and practical reflections on philosophical and anthropological phenomena. St. Francis’ Christocentric anthropology was understood as opposed to the anthropology of domination. Interest of philosophy to this last is quite natural if we consider philosophy as the ability to surprise, as the source of joy, humility before the diversity of the world and childishness close to buffoonery. Keywords: St. Francis of Assisi, Franciscanism, modernism, postmodernism, philosophical anthropology, joy, freedom.